SISTEM PENGATURAN SALINITAS PADA AKUARIUM IKAN KOI MENGGUNAKAN MOTOR SERVO BERBASIS LOGIKA FUZZY METODE SUGENO - Dean Passaddhi; n/a Rahmadwati; Eka Maulana (Jurnal Mahasiswa TEUB, 2022)
Koi fish (Cyprinus carpio), or commonly known as nishikigoi, is one of the ornamental fish that is in great demand by the public today, because koi fish has a very beautiful uniqueness, both in terms of shape, pattern, and color on the body of the koi fish, that it has a high selling price. Maintaining koi fish is a small-scale cultivation activity, which is currently popular with the public during this pandemic, but maintaining a koi fish is complicated because there are many factors that need to be considered so that the health of koi fish is maintained, especially where koi fish live in the form of water. Basically, fish will live and breed in an aquarium properly if the environmental conditions provided in accordance with their living conditions can be met or close to their natural habitat, one of the water parameters that needs to be considered is salinity. Koi fish are sensitive to salt concentrations in their environment and have developed systems that maintain a constant balance of salt ions in their bloodstream through the movement of salts and across gill membranes. Koi fish have a minimum salinity level of 2 ppt and a maxi